Histone deacetylation contributes to low extracellular superoxide dismutase expression in human idiopathic pulmonary arterial hypertension - Nozik-Grayck, Eva; Woods, Crystal; Stearman, Robert S.; Venkataraman, Sujatha; Ferguson, Bradley S.; Swain, Kalin; Bowler, Russell P.; Geraci, Mark W.; Ihida-Stansbury, Kaori; Stenmark, Kurt R.; McKinsey, Timothy A.; Domann, Frederick E. (American journal of physiology. Lung cellular and molecular physiology, 2016)
Epigenetic mechanisms, including DNA methylation and histone acetylation, regulate gene expression in idiopathic pulmonary arterial hypertension (IPAH). These mechanisms can modulate expression of extracellular superoxide dismutase (SOD3 or EC-SOD), a key vascular antioxidant enzyme, and loss of vascular SOD3 worsens outcomes in animal models of pulmonary arterial hypertension. We hypothesized that SOD3 gene expression is decreased in patients with IPAH due to aberrant DNA methylation and/or histone deacetylation. We used lung tissue and pulmonary artery smooth muscle cells (PASMC) from subjects with IPAH at transplantation and from failed donors (FD). Lung SOD3 mRNA expression and activity was decreased in IPAH vs. FD. In contrast, mitochondrial SOD (Mn-SOD or SOD2) protein expression was unchanged and intracellular SOD activity was unchanged. Using bisulfite sequencing in genomic lung or PASMC DNA, we found the methylation status of the SOD3 promoter was similar between FD and IPAH. Furthermore, treatment with 5-aza-2′-deoxycytidine did not increase PASMC SOD3 mRNA, suggesting DNA methylation was not responsible for PASMC SOD3 expression. Though total histone deacetylase (HDAC) activity, histone acetyltransferase (HAT) activity, acetylated histones, and acetylated SP1 were similar between IPAH and FD, treatment with two selective class I HDAC inhibitors increased SOD3 only in IPAH PASMC. Class I HDAC3 siRNA also increased SOD3 expression. Trichostatin A, a pan-HDAC inhibitor, decreased proliferation in IPAH, but not in FD PASMC. These data indicate that histone deacetylation, specifically via class I HDAC3, decreases SOD3 expression in PASMC and HDAC inhibitors may protect IPAH in part by increasing PASMC SOD3 expression.